The Effectiveness of Customary International Law: Stephen Lushington and the Trent Affair - Peter R. Castro (Washington University Global Studies Law Review, 2023)
This essay is an empirical study of the actual influence or effectiveness of customary international law in foreign-affairs crises. In 1968, Professor Louis Henkin asserted “it is probably the case that almost all nations observe almost all principles of international law and almost all their obligations almost all the time.” Since that time, a number of capable theorists have explored his assertion.Some have advanced a theory of constructivism in which foreign-policy actors internalize a conviction that international law principles are legitimate and should be followed. Others endorse a rational-choice approach, which emphasizes a state’s perceived self-interest. The present essay examines the role that these two theories played in a specific foreign-affairs crisis. International law theorists have distinguished between compliance and effectiveness.Compliance refers to theories that explain why state action generally conforms to international law. These theories are like the hypotheses in our junior-high explorations of the beloved scientific method. In contrast, effectiveness is concerned with empirical causation. Does international law actually influence state action? Compliance theories are closely related to effectiveness, but they are theories and do not directly address the issue of effectiveness. They are hypotheses that need to be tested.
Keywords: Customary International Law; Foreign-Affairs; Crises; constructivism; compliance; effectiveness; Theory; International Law